Antisemitism in America - Dinnerstein, Leonard (Oxford University Press, 1995)
Is antisemitism on the rise in America? A glance at the daily newspapers suggests a resurgence of animosity yet Leonard Dinnerstein, in this provocative and in-depth study, categorically states that there is less bigotry in this country than ever before. He also argues in this provocative analysis that Jews have never been more at home in America. What we are seeing today, he writes, is media hype. A long tradition of prejudice, suspicion, and hatred against the Jews, the direct product of Christian teachings, has, in fact, finally begun to wane. In Antisemitism in America, Dinnerstein provides a landmark work - the first comprehensive history of prejudice against Jews in the United States, ranging from its foundations in European Christian culture to the present day. Dinnerstein's richly detailed and thoroughly documented book reveals how Christians carried their religious prejudices with them to the New World and how they manifested themselves, albeit in muted form, in the colonial wilderness and in the developing American society thereafter. Jews could not vote, for example, in Rhode Island or New Hampshire until 1842, and in North Carolina until 1868. The Civil War witnessed the first major wave of publicly displayed American antisemitism as individuals in both the North and the South assumed that Jews sided with the enemy. The decades that followed marked the emergence of a full-fledged antisemitic society as Christians excluded Jews from their social circles and wove fantasies for themselves as they pictured what "Jews were really like." Antisemitic fervor mixed with racism at the beginning of the twentieth century, accelerated by the views of eugenicists, fears of Bolshevism, and the rantings of Henry Ford. During the Depression hostility toward Jews accelerated as Americans vented their frustrations upon minorities because of the economic crises of the decade. Christians of all stripes called upon Jews to accept the divinity of Jesus Christ, and Father Charles Coughlin emerged as one of the most beloved priests in all of American history as he excoriated Jews and sympathized with Nazis over the airwaves and in his journal, Social Justice. Ironically, Dinnerstein writes, as Americans fought in World War II to make the world safe for democracy, public opinion polls noted a huge increase in American animosity toward Jews. Not until after the war ended did this enmity subside. While fresh economic opportunities and, heightened sensitivities to the effects of bigotry resulted in the decline of all prejudices in this country, including antisemitism, it nevertheless still cropped up in the highest ranks of government. especially during Richard Nixon's presidency. Within this volume, Dinnerstein not only chronicles the growth, demise and manifestations of antisemitism on the national scene but devotes individual chapters, as well, to the South and to African Americans, showing that prejudice among both whites and blacks below the Mason-Dixon line flowed from the same stream of Southern evangelical Christianity. "It must also be emphasized," Dinnerstein writes, "that in no Christian country has antisemitism been weaker than it has been in the United States," with its traditions of tolerance, diversity, and a secular national government. This book, however, reveals in disturbing detail the resilience, and vehemence, of this ugly prejudice. Penetrating, authoritative, and frequently alarming, this is the definitive account of a plague that apparently has a life of its own.